2022
DOI: 10.3390/ijms23031786
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Inflammation and Pathological Bone Resorption: Insights into Recent Mechanisms and Pathways in Related Diseases for Future Perspectives

Abstract: Bone is a mineralized and elastic connective tissue that provides fundamental functions in the human body, including mechanical support to the muscles and joints, protection of vital organs and storage of minerals. Bone is a metabolically active organ that undergoes continuous remodeling processes to maintain its architecture, shape, and function throughout life. One of the most important medical discoveries of recent decades has been that the immune system is involved in bone remodeling. Indeed, chronic infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 179 publications
(222 reference statements)
0
34
0
Order By: Relevance
“…Many factors, including fractures, may result in increased oxidative damage via inflammatory pathways and so on, which may consume the efficiency of the antioxidant defense system. 7 , 10 Therefore, we believe that the patients with high SOD or GR may have strong abilities to defend their bones from oxidative stress, and then are more likely to have a more satisfactory rehabilitation. Many studies had shown how the status of oxidative stress impacts bone remolding and bone healing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many factors, including fractures, may result in increased oxidative damage via inflammatory pathways and so on, which may consume the efficiency of the antioxidant defense system. 7 , 10 Therefore, we believe that the patients with high SOD or GR may have strong abilities to defend their bones from oxidative stress, and then are more likely to have a more satisfactory rehabilitation. Many studies had shown how the status of oxidative stress impacts bone remolding and bone healing.…”
Section: Discussionmentioning
confidence: 99%
“… 6 After the fracture, the broken end of the bone may stimulate inflammation by releasing inflammatory factors and promoting the chemotactic movement of immunocytes. 7 The inflammation causes cellular damage, and then free radicals, such as reactive oxygen species (ROS) and reactive nitrogen species (RNS), were accumulated, resulting in oxidative stress. 8 Oxidative stress may interrupt the balance of bone metabolism and lead to abnormal bone generation, which makes patients who are suffering fractures have long bed-stay, fracture nonunion, and poor outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…We inspected that several osteoclasts generated on the inflammatory bone surface, accompanying large amounts of inflammatory cytokines produced and released by multiple immune cells, which was in line with the previous study ( Kumar and Roger, 2019 ). The evidence is clear that some proinflammatory cytokines, like TNF and IL-1, regulate the activation of calcium signaling and NFATc1, which subsequently activate genes related to osteoclastogenesis and osteoclast function ( Kim et al, 2013 ; Terkawi et al, 2022 ). It is obvious that inflammatory stimulation induces bone resorption and leads to bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…The signaling pathways for NF-κB and c-src/PI 3-kinase/Akt are started when these immune factors activate TNF-related factors (TRAFs). Activating downstream molecules like c-Fos and Fos B causes the nuclear factor of activated T-cells cytoplasmic 1 (NFATc1) to be produced, which in turn causes the maturation and activation of osteoclasts ( 30 ). An immunoclinical study shows that CD19+ B lymphocytes are less abundant in postmenopausal women, however, they secrete more granulocyte-macrophage-colony-stimulating factor (GM-CSF) ( 31 ).…”
Section: Pathological Changes Mechanism Of Opmentioning
confidence: 99%